Risk factors for prognoses of uremic maintenance dialysis patients with novel coronavirus infection - Wen-jiang Gong; Ming-yu Cai; Jing-fang Wan; Li-li Fu; Shi-hui Hou; Jie Yang (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To retrospectively explore the prognostic factors of uremic maintenance hemodialysis （MHD） patients with novel COVID-19 infection. Methods A total of 556 MHD patients on regular follow-ups were recruited. Baseline profiles and laboratory tests were recorded prior to contracting COVID-19 infection. Results There were 312 males and 244 females with an age of （52.37 ± 14.81） year and an MHD duration of （61.02 ± 43.90） months. Diabetic kidney disease（DKD） was a primary disease （n = 101, 18.1%） with top three complications of diabetes mellitus （DM）（n = 135, 16.3%）, cardiovascular disease （CVD）（n = 48, 6.6%） and stroke （n = 3, 0.5%）. Hemodialysis （n = 192, 34.5%） and peritoneal dialysis （PD）（n = 364, 65.5%） were performed. DM, hemodialysis, age and serum sodium level were risk factors for mortality after COVID-19 infection. And serum prealbumin level was a protective factor. Multivariate regression analysis revealed that MHD and age were independent risk factors for mortality. Cardiovascular disease, MHD, age and blood glucose level were risk factors for severe pneumonia after COVID-19 infection. And serum albumin level was a protective factor. Conclusion CVD and hyperglycemia are independent risk factors for severe pneumonia while age is an independent risk factor for severe pneumonia and mortality. Generally MHD patients have a higher risk of mortality than PD counterparts.